A A retrospective study on the effectiveness of active surveillance, control and prevention of the outbreak of COVID-19 in rural communities, Ron Phibun District Nakhon Si Thammarat Province - Thunboonyakid, Siritun; Sukchan, Phnom; Sangsri, Tanes (Princess of Naradhiwas University Journal, 2023)
The spread of Coronavirus disease 2019 (COVID -19) has had a significant impact on public health, medical, social, and economic systems. This study aimed to analyze the utilized multiple interventions and control measures for the outbreak of COVID-19 in the rural community, Ron Phibun district, Nakhon Si Thammarat Province. A descriptive study was conducted to review all laboratory-confirmed COVID-19 case investigation reports and identify active measures from April 24 to May 20, 2021. A total of 80 laboratory-confirmed COVID-19 cases were identified in the Ron Phibun district; 80 cases were detected via active surveillance measures, with 17 (21.25%) identified through active case finding, 33 (41.25%) through close contact tracing, and 30 (37.5%) through the surveillance system. The median age of 80 cases was 39 years (Q1=19, Q3=51). The analytic result showed that the group of household contacts and Buddhist ordination ceremony of the confirmed cases had a higher risk of SARS-CoV-2 infection than community contacts. This study indicated that prevention and mitigation of a super-spreading event require decisions that are based first and foremost on quickly recognizing and comprehending these events, especially in healthcare settings, identifying and mitigating high-risk settings, and strict adherence to active measures. Suggestions based on research findings to inform public health policies should be strengthened timely implementation of nonpharmaceutical interventions could all help in the prevention and control of the COVID-19 outbreak, and when future infectious disease outbreaks in a similar context.